To Be Real, or Not To Be Real, That Is The Question: A Content Analysis of Augmented Reality Articles in Advertising and Marketing Journals from 2017 to 2021 - Damla Karşu Cesur (Medya ve Kültür)
This study focuses on 24 published augmented reality (AR) articles in top-tier SSCI indexed advertising and marketing journals with high SJR rankings between 2017 and 2021. Employing a content analysis frame of Yale and Gilly (1988), the study aims to provide insight for further AR-related research that could “augment” the advertising and marketing literature. The findings reveal that most of the current articles were related to consumer behavior and primarily addressed scholars and managers. It is also observed that quantitative methodology and experiments were adopted mainly. The most statistical analysis performed in these articles was meditation analysis, while the research respondents were generally students.